Making lighting adjustments to establish new behavioral patterns in a child with autism: A follow-up study. - PIVEN, Emily; DERAKHSHANRAD, Seyed Alireza (Iranian Journal of Child Neurology)
Objectives Acknowledging the importance of lighting adjustment (a less-studied aspect of the environmental modification), this study showed novel effects of black light conditions, where white objects became part of the foreground of a blackened environment to train a child with autism to master a series of self-care tasks. This follow-up study provided details about how training progressed under black light conditions to teach the child a second task called self-feeding. The process of training self-feeding for this child was undergone after the child mastered the self-care task of toothbrushing. Healthcare practitioners may want to illuminate overlooked aspects of the non-human environment, which may be ignored by children with autism, to stimulate interest in objects following lighting adjustments.